Cognitive Ability and Non-Ability Trait Predictors of Academic Achievement: A Four-Year Longitudinal Study - Phillip L. Ackerman; Ruth Kanfer (Journal of Intelligence, 2025)
Prediction of individual differences in academic achievement is one of the most prominent longstanding goals of differential psychology. Historically, the main source of prediction has been measures of intelligence and related cognitive abilities. Researchers have suggested that non-ability traits, such as personality, may also provide useful information in predicting academic achievement. Meta-analyses have indicated that there are significant correlations between such variables, but most of the existing studies have been conducted with cross-sectional designs, or with a limited inclusion of intelligence/cognitive ability variables, making it difficult to determine whether the non-ability measures provide incremental predictive validity for academic achievement. In this longitudinal study, both extensive cognitive ability and non-ability trait measures (personality, interests, self-concept/self-estimates of abilities, and motivational traits) were administered at the beginning of secondary school, and criterion measures of ability and academic achievement were obtained after four years of secondary school. The results indicate that although non-ability trait measures have significant and meaningful correlations with the criterion measures, their incremental predictive validity over cognitive abilities alone is somewhat diminished. Nonetheless, there is potential utility for including assessments of non-ability traits for predicting future academic performance and elective course enrollments.